INTEGRATING COMMUNICATIVE TASKS AND COGNITIVE APPROACH IN ENGLISH LANGUAGE SPEAKING SKILLS AT SMPN 3 BAJENG - Sabar, Surahmi; Nappu, Syamsiarna; Junaid (FKIP Unismuh Makassar, 2024)
This thesis aims to find out the effect of Integrating Communicative tasks and Cognitive Approaches on students’ English Language Speaking skills in terms of pronunciation and fluency for the first grade of SMPN 3 Bajeng.Pre-test and post-test were employed in this pre-experimental study. The kids at SMP Negeri 3 Bajeng VII grade make up the population of this study, and the researcher employed random cluster sampling to create the sample. The study's sample consisted of 27 pupils. A speaking test with 4 questions served as the research tool.The analysis of the data reveals that before the treatment, there was a difference in the scores of the students taking the pre-test and post-tests. The fact that the post-test score of 57.40 is greater than the pre-test average of 35.18 indicates that pupils have improved their pronunciation skills. Pre-test 34.25 and post-test 64.81 together demonstrate the student's fluency's mean score. Additionally, it was determined through the t-test analysis that the t-test value was higher than the t-table; the value was 11.83>2.05. Hypothesis (H0) is rejected and the Alternative Hypothesis (H1) is accepted as the result of this study's hypothesis. It means that integrating communicative tasks and cognitive approach has an effect on the pronunciation and fluency of students in speaking skills.